Design and experimental validation for nonlinear control of internal combustion engines with EGR and VVT. Issue 1 (1st January 2021) - Shi, Haoyun; Shen, Tielong
Abstract : This paper presents a feedback control design scheme for internal combustion engines with the exhaust gas recirculation and the variable valve timing. A second-order nonlinear dynamical model is presented for describing the transient behaviour of the engine. According to a given operating point of the engine coordinated by the speed and the torque, seeking approach for the optimal set-point with respect to the cost function of fuel consumption is shown that provides the equilibrium of the dynamic model. Then, a state feedback control law is constructed based on Lyapunov stability theory to render the closed-loop error system converge to zero. Finally, experiment validation results conducted on a full-scaled engine control test-bench are demonstrated.